A systematic review and meta-analysis of nutritional and dietary interventions in randomized controlled trials for skin symptoms in children with atopic dermatitis and without food allergy : An EAACI task force report - Vassilopoulou, Emilia; Comotti, Anna; Douladiris, Nikolaos; Konstantinou, George Ν.; Zuberbier, Torsten; Alberti, Ilaria; Agostoni, Carlo; Berni Canani, Roberto; Bocsan, Ioana Corina; Corsello, Antonio; De Cosmi, Valentina; Feketea, Gavriela; et al. (Wiley-Blackwell, 2025)
This systematic review and meta-analysis aimed to consolidate evidence on dietary interventions for atopic eczema/dermatitis (AD) skin symptoms in children without food allergies, following PRISMA 2020 guidelines. Systematic review updates were conducted in May 2022 and June 2023, focusing on randomized placebo-controlled trials (RCTs) involving children with AD but without food allergies. Specific diets or supplements, such as vitamins, minerals, probiotics, prebiotics, symbiotics, or postbiotics, were explored in these trials. Exclusions comprised descriptive studies, systematic reviews, meta-analyses, letters, case reports, studies involving elimination diets, and those reporting on food allergens in children and adolescents. Additionally, studies assessing exacerbation of AD due to food allergy/sensitization and those evaluating elimination diets' effects on AD were excluded. Nutritional supplementation studies were eligible regardless of sensitization profile. Evaluation of their impact on AD clinical expression was performed using SCORAD scores, and a meta-analysis of SCORAD outcomes was conducted using random-effect models (CRD42022328702). The review encompassed 27 RCTs examining prebiotics, Vitamin D, evening primrose oil, and substituting cow's milk formula with partially hydrolyzed whey milk formula. A meta-analysis of 20 RCTs assessing probiotics, alone or combined with prebiotics, revealed a significant reduction in SCORAD scores, suggesting a consistent trend in alleviating AD symptoms in children without food allergies. Nonetheless, evidence for other dietary interventions remains limited, underscoring the necessity for well-designed intervention studies targeting multiple factors to understand etiological interactions and propose reliable manipulation strategies.